ROLE OF SERUM ZINC AND COPPER AND ZINC/ COPPER RATIO IN ALOPECIA AREATA - Ashwaq Najjem Elldin Al- Jaff (College of Pharmacy University of Baghdad, 2017)
ABSTRACT: Alopecia areata is considered as a major health problem, its importance is attributed to its recent increased incidence in our population. Till now, there is no exact cause for alopecia areata although researchers thought it's an autoimmune disease. This clinical study was designed to evaluate the role of trace elements (zinc and copper) in patients with alopecia areata. Twenty patients were diagnosed as having alopecia areata with an age range (10-40 years) were involved in this study. Normal subjects of the same age group were also evaluated as control. The level of serum Zn and Cu were measured by flame atomic absorption spectrophotometry in both control and patient group. And the ratio of Zn/Cu was also estimated. The results of patients group revealed that serum Zn level was significantly lower than those of control (p<0.001), while serum Cu was significantly higher than that of control group (p=0.002). Furthermore, Zn/Cu ratio of patients group was significantly lower than that of control subjects (p<0.001). These results suggest the possible role of Zn and Cu level in alopecia areata. In addition to that the utility of measuring Zn/ Cu ratios for the diagnosis of the disease over that of determining the serum level of Zn or Cu alone since this ratio clearly reflects the severity of the progress.